Zakład lecznictwa uzdrowiskowego. Część 2. Status prawny organów zakładowych podmiotu leczniczego i personel uzdrowiskowy zakładu - Jachimowicz-Jankowska, Paulina (Studia Prawa Publicznego, 2021)
The spa treatment facility located in the health resort is distinguished by its specificity due to the fact that it conducts spa treatment in this type of medical entity. For the proper performance of the healing function and offering the health services for which a given spa is intended, the human factor plays an important role, taking into account the specificity of the health resort. This applies to those constituting the authorities of a health resort treatment facility, namely the manager and social committee (which in this study are limited to non entrepreneurs), as well as medical professionals and other employees. The special powers of the authorities and staff of spa treatment facilities towards the people using the health services provided there are reflected in the sources of law, which include the statute and organizational regulations of this type of medical facility. The article contains an analysis and assessment of legal regulations relating to the scope of the activities of the authorities of this type of spa treatment facilities, with particular emphasis on the manager and social council and staff, especially person body plays a fundamental role in managing a medical facility, with responsibility for management and for all facility employees. On the other hand, the social committee, which is the collegiate body of this institution, is appointed only in a non-entrepreneurial medical facility, and this body is characterized by a specific legal nature that performs various tasks. The efficient operation of the plant is also ensured by professional medical staff, other medical workers and other employees. The legal status of company bodies and personnel is presented in terms of generally applicable regulations, as well as in the context of the organizational regulations and the statute of the spa treatment facility.